2021
DOI: 10.1515/sjpain-2021-0069
|View full text |Cite
|
Sign up to set email alerts
|

Circulating long non-coding RNA signature in knee osteoarthritis patients with postoperative pain one-year after total knee replacement

Abstract: Objectives The incidence of chronic postoperative pain after total knee replacement (TKR) is approx. 20%, and hence preoperative risk factors are important to identify. Recent studies have indicated that preoperative inflammatory markers might hold prognostic information for the development of chronic postoperative pain. Long non-coding RNA (lncRNA) regulates the expression of genes related to e.g. inflammatory processes. The current study aimed to investigate the preoperative lncRNA signatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 59 publications
(70 reference statements)
0
10
0
Order By: Relevance
“…( 64,65 ) MALAT1 itself appears to inhibit senescence, evident from experiments where MALAT1 siRNA increased senescent cell numbers in vitro. ( 64 ) Importantly, MALAT1 decreases in patients with osteoarthritis, ( 66 ) in patients with postmenopausal osteoporosis, ( 67 ) and in mouse muscle atrophied with aging, hindlimb unloading, and glucocorticoid treatment ( 63,68 ) (Fig. 3).…”
Section: Discussionmentioning
confidence: 97%
“…( 64,65 ) MALAT1 itself appears to inhibit senescence, evident from experiments where MALAT1 siRNA increased senescent cell numbers in vitro. ( 64 ) Importantly, MALAT1 decreases in patients with osteoarthritis, ( 66 ) in patients with postmenopausal osteoporosis, ( 67 ) and in mouse muscle atrophied with aging, hindlimb unloading, and glucocorticoid treatment ( 63,68 ) (Fig. 3).…”
Section: Discussionmentioning
confidence: 97%
“…Preoperative dysregulation of circulating microRNAs and long non-coding RNA (lncRNA) related to the inflammatory processes may serve as predictive biomarkers of pain outcome after surgery. 33 , 34 The hookwire localization may trigger releases of inflammatory mediators. In this study, we did not measure preoperative serum levels of inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a study of 20 preoperative KOA patients revealed that serum levels of MZF1-AS1, MALAT1, and LOC100287846 were lower preoperatively in the chronic postoperative pain group ( n = 10) compared to the normal postoperative pain recovery group ( n = 10). 56 Thus, in addition to miRNAs, biofluid lncRNAs may also be good candidate biomarkers for OA diagnosis, prognosis, and therapeutic efficacy tracking. More extensive studies investigating lncRNAs, their links to individual miRNAs, and changes with OA stage, symptoms and outcomes are necessary.…”
Section: Emerging Molecular Biomarkersmentioning
confidence: 99%